2011
DOI: 10.1063/1.3660677
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of glow-plasma structure in atmospheric radio frequency microplasmas at very small gaps

Abstract: In atmospheric radio frequency discharges at 13.56 MHz, with the electrode gap reduced, the sheath region eventually occupies a main portion of the electrode spacing and the bulk plasma region is significantly compressed. The computational results in this letter based on a one-dimensional fluid model show that by increasing the excitation frequency over 13.56 MHz, the traditional glow-plasma structure could gradually recover even at very small sizes with a well defined quasineutral plasma region, and the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
(37 reference statements)
0
20
0
3
Order By: Relevance
“…Moreover, an electron-heating mode and its transition, which are induced by changes in the input power and frequency, have been reported as in the cases of low-pressure discharges. 9,[13][14][15] However, the previous studies of the electron-heating mode were based on fluid models; 11,12 the effects of heating on the electron kinetics has not yet been clarified. In particular, we are interested in the electron energy distribution function (EEDF) on the electrodes in atmospheric discharges for biomedical applications.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, an electron-heating mode and its transition, which are induced by changes in the input power and frequency, have been reported as in the cases of low-pressure discharges. 9,[13][14][15] However, the previous studies of the electron-heating mode were based on fluid models; 11,12 the effects of heating on the electron kinetics has not yet been clarified. In particular, we are interested in the electron energy distribution function (EEDF) on the electrodes in atmospheric discharges for biomedical applications.…”
Section: Introductionmentioning
confidence: 98%
“…1-8 For atmospheric radio-frequency (rf) capacitive discharges, a variety of microplasmas operating over a wide range of frequencies and sub-millimeter dimensions have been reported. 1,4,[9][10][11][12] We previously studied single-frequency (SF) 9 and dual-frequency (DF) 10 atmospheric-pressure helium microplasmas, which can be sustained over a wide range of microwave frequencies from 400 MHz to 2.45 GHz. These microwave-induced microplasmas are important because they may be used to develop safe, portable, and long-lifetime devices capable of operating at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The current density with a normal sinusoidal form is taken as the input parameter [4], [6], [24], and the driving frequency is 13.56 MHz; the coupled power, actually the power per area as a result of 1-D limit, is usually fixed, to reasonably compare the evolution of discharge. The present model with pure helium as working gas has been explored to investigate the discharge characteristics at very small gaps [22], and the simulation results show a good agreement of experimental observation [21]. As the oxygen admixture was introduced, the discharge characteristics and generation of ROS at a relatively large electrode gap also have been investigated and compared with the experimental measurements [13].…”
Section: Description Of Plasma Modelmentioning
confidence: 72%
“…The fundamental physics of RF discharges shows some unique characteristics features in microplasma regime, which have been discussed in detail in [17]- [19]. A sheath-dominated structure with a large portion of sheath region has usually been observed, and a traditional glowdischarge structure with a distinct bulk plasma and sheath could not be formed in RF microplasmas [20], [21]; in addition, the recent computational study indicated that the glow-discharge structure could also be recovered by increasing the excitation frequency even at very small gaps [22]. However, when the oxygen admixtures are added into helium microplasmas, plenty of new neutral and charged particles will be generated, and this could influence the evolution of discharge structure.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8] In particular, for atmospheric radio-frequency (rf) capacitive discharges, a large variety of single-frequency (SF) microplasmas that operate over a wide range of frequencies and sub-millimeter dimensions have been reported. 1,4,[9][10][11] Especially, in our previous study, 9 SF atmospheric-pressure helium microdischarges sustained over a wide range of microwave frequencies were the focus of our investigation. The microplasmas generated in these studies showed unique properties, such as highly energetic electrons, different discharge structures, and non-equilibrium characteristics.…”
Section: Introductionmentioning
confidence: 99%